1995
DOI: 10.1259/0007-1285-68-813-973
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of iodixanol with iopamidol in aorto-femoral angiography

Abstract: This double-blind, randomized, parallel group clinical investigation in 140 consecutive patients undergoing aorto-femoral arteriography was carried out to compare iodixanol (Visipaque) 270 mgI ml-1 with iopamidol (Iopamiro) 300 mgI ml-1. The aims of the study were to compare adverse events and discomfort, clinical chemistry parameters in blood, haemodynamics and diagnostic information of the angiograms in the two groups. The main parameter for statistical analysis was the visual analogue scale (VAS) score for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 24 publications
4
25
0
Order By: Relevance
“…11 Our findings in relation to contrast tolerability and symptoms are consistent with findings by Svensson et al 7 which showed that iodixanol-320 injection was associated with less heat sensation compared with iomeprol-400 in patients undergoing MDCT-CA 7 and with 2 other studies showing that leg pain was reduced during femoral arteriography performed with iodixanol compared with 2 low-osmolar CM. 12,13 With regard to the lower number of slice misalignment artifacts with iodixanol, our results indicate that this was likely because of the reduction of arrhythmias and more stable HR during the scan after iodixanol-320 administration. This is in agreement with the study by Svensson et al 7 which reported a reduction of PHBs with iodixanol-320 compared with iomeprol-400 during MDCT-CA and with other clinical and animal studies that showed fewer electrophysiological changes and proarrhythmic effects of iodixanol-320 than of low-osmolar agents that were attributed to the electrolyte composition of the isoosmolar CM.…”
Section: Discussionmentioning
confidence: 73%
“…11 Our findings in relation to contrast tolerability and symptoms are consistent with findings by Svensson et al 7 which showed that iodixanol-320 injection was associated with less heat sensation compared with iomeprol-400 in patients undergoing MDCT-CA 7 and with 2 other studies showing that leg pain was reduced during femoral arteriography performed with iodixanol compared with 2 low-osmolar CM. 12,13 With regard to the lower number of slice misalignment artifacts with iodixanol, our results indicate that this was likely because of the reduction of arrhythmias and more stable HR during the scan after iodixanol-320 administration. This is in agreement with the study by Svensson et al 7 which reported a reduction of PHBs with iodixanol-320 compared with iomeprol-400 during MDCT-CA and with other clinical and animal studies that showed fewer electrophysiological changes and proarrhythmic effects of iodixanol-320 than of low-osmolar agents that were attributed to the electrolyte composition of the isoosmolar CM.…”
Section: Discussionmentioning
confidence: 73%
“…According to this result, the fixed effects model was chosen to test the overall effect. The test for the overall effect showed a significant difference in favor of the group receiving IOCM, with the odds ratio (OR) ϭ 0.39, 95% confidence interval (CI) 0.23 to 0.66, p ϭ 0.0004 (19,20,25,26,30,(32)(33)(34)(35)(36). Heterogeneity test for trials in which at least 1 patient experienced CIN (10 of 16), and test for the overall effect with trials weighted according to the Mantel-Haenszel method, with the Review Manager 4.2.7. n ϭ number of patients who experienced CIN defined as Cr increase Ն0.50 mg/dl; N ϭ number of patients with Cr measurements; PTCA ϭ percutaneous transluminal coronary angioplasty (trial [25]); other abbreviations as in Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Several studies that have compared the tolerability of the iso-osmolar contrast medium iodixanol with that of lowosmolar contrast medium report that iso-osmolar contrast medium is associated with a decrease in the intensity of discomfort (heat sensations) and pain. [24][25][26][27][28][29][30] Overall, the key issue that becomes important to define for each specialty is the degree of risk that makes the effort needed to screen patients, identify those at risk, and then implement prevention strategies, a requirement despite any impracticality.…”
Section: The Need For Specialty-specific Guidelinesmentioning
confidence: 99%